Normal-weight obesity in high-altitude youth: Gender disparities and protective effects of native adaptation - Nanhui Peng; Jia Li; Baifang Liu; Xu Yan; Nima Ouzhu (PLoS ONE, 2025)
Background While high altitude has been associated with reduced muscle mass, its effects on fat mass remain controversial, with studies reporting both fat accumulation and loss. Normal weight obesity (NWO), characterized by normal body mass index (BMI) but excessive body fat, is an emerging metabolic health concern. This study aimed to investigate the prevalence of NWO among young adults in a high-altitude region, while also analyzing body composition differences between genders, as well as native versus migrant populations. Methods In this cross-sectional study, 1,313 university students (mean age: 19.6 ± 1.6 years; 719 females and 594 males; all enrolled in undergraduate studies) from Lhasa, Tibet (altitude: 3,650m), who voluntarily participated in body composition measurements during the university’s annual physical fitness assessments. The participants were from multiple academic departments. They underwent anthropometric and body composition assessments, including body fat percentage (BF%), fat-free mass (FFM), skeletal muscle mass (SMM), and waist-to-hip ratio (WHR). Participants were stratified by BMI and BF% to determine NWO prevalence, with subgroup analyses for gender and residential background. Results BF% trends varied by gender; female students showed a linear increase with BMI, while male students exhibited a phased pattern with two turning points at BMI = 19.6 and 26.5. The overall prevalence of NWO among high-altitude university students was 22.2%, accounting for 57% of individuals with excessive body fat. Females were disproportionately affected (27.7% vs.16.7% in males). Both females and males with NWO had significantly lower FFM and SMM than their non-NWO counterparts (P < 0.001). A subset analysis of 389 individuals revealed that NWO incidence was significantly lower among high-altitude native females and males compared with their migrant counterparts. Among those with NWO, migrant females had a higher BF% (P = 0.02), whereas native males exhibited a higher WHR (P = 0.009). Conclusions NWO prevalence among young adults in a high-altitude region was comparable to lowland populations, with notable gender disparities. NWO was associated with reduced muscle mass, suggesting elevated metabolic health risks. The lower NWO prevalence among native high-altitude residents suggests potential protective effects associated with chronic hypoxia adaptation. These findings underscore the need for further research to elucidate the complex relationship between chronic hypoxia, body composition, and metabolic health in high-altitude populations. Such insights are crucial for developing targeted interventions addressing normal weight obesity.